Nivel y standard de vida de algunas familias rurales en seis comunidades rurales de Costa Rica - Cordeiro, C. de A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A survey was conducted to determine the levels (items possessed) and standards (items desired) of living of some farm families in six communities of Costa Rica. Two questionnaires were used, along with a level of living scale constructed by Collazo for Puerto Rico. Positive relationships were found between the level of education, income, size of farms, and the level of living of farmers. The evidence was unsatisfactory in regard to the desire for some fundamental needs. Due to the low standard of living found, it is possible that this lack of knowledge, overly influenced the farmers choice. The Collazo level of living scale can be used in other Latin American countries as long as scales are not made up for each country. It is concluded that the questionnaire on aspirations ought to be modified having in mind the lack of knowledge of many items by farmers.